Combining Theory and Research to Validate a Social Norms Framework Addressing Female Genital Mutilation - Sood, Suruchi; Ramaiya, Astha (Frontiers in Public Health, 2022)
Female Genital Mutilation (FGM) is a harmful practice with no benefits and considerable harm to girls and women who undergo it. In 2016, the United Nations Joint Program to Eliminate FGM, funded the development and subsequent validation of a monitoring and evaluation framework to understand the relationship between social norms and practicing FGM. Evidence on the framework was gathered through a pilot study in Ethiopia. This paper uses cross-sectional quantitative data from the pilot to operationalize the framework and determine what factors are associated with practicing FGM. A total of 554 and 481 participants answered the question “Have you undergone FGM?” and “Do you know a family member who has undergone FGM?” respectively. Overall, 65% of participants said they had undergone FGM and 32% said they knew someone in their family who had undergone FGM. Predictors of not undergoing FGM included most progressive attitudes vs. less progressive attitudes about FGM and relationship to identity [OR: 1.9 (95% CI: 1.1–3.3)]; region [Afar vs. Addis Ababa: OR: 0.09 (95% CI: 0.02–0.5); Southern Nations Nationalities and People's Regions vs. Addis Ababa: OR: 0.1 (95% CI: 0.05–0.3)], being 36 years old and above vs. 10–19 years (OR: 0.2 (95% CI: 0.1 to 0.7)) and being single, never married vs. married or engaged (OR: 2.8 (95% CI: 1.1–7.0)]. Predictors of knowing a family member who has not undergone FGM included: Higher knowledge vs. lower knowledge [OR: 0.3 (95% CI: 0.1–0.5)]; if the family expected you to abandon FGM, you had a greater odds of knowing a family member who had not undergone FGM [43.6 (95% CI: 2.7–687.8)]; coming from Southern Nations, Nationalities and People's Region was associated with a lower odds of knowing a family member who had not undergone FGM [0.3 (95% CI: 0.1–0.6)]. Being a female influential vs. female caregiver was associated with a higher odds of knowing a family member who had not undergone FGM [2.9 (95% CI: 1.01–5.2)]. This paper has allowed us to validate a theory and research based social norms framework, specifically examining how social and behavior change communication can be used as a mechanism for shifting norms around a given harmful practice. Now that this model has been developed and validated, it is likely to provide a foundation to study the direct and indirect impacts of social norms programming on changing harmful practices, such as FGM.